2004
DOI: 10.4049/jimmunol.173.11.6921
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor and Kinin-Dependent Vascular Leakage as a Novel Functional Activity of the Soluble Terminal Complement Complex

Abstract: The infrequent occurrence of septic shock in patients with inherited deficiencies of the terminal complement components experiencing meningococcal disease led us to suspect that the terminal complement complex is involved in vascular leakage. To this end, the permeabilizing effect of the cytolytically inactive soluble terminal complement complex (SC5b-9) was tested in a Transwell system measuring the amount of fluorescein-labeled BSA (FITC-BSA) leaked through a monolayer of endothelial cells. The complex cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 39 publications
1
79
0
2
Order By: Relevance
“…FITC-dextran (70 kDa; Sigma-Aldrich) was injected at 10 mg/kg body weight into the retro-orbital plexus as a plasma tracer to permit visualization in fluorescence light of changes in vascular permeability. After topical application of FXIIa (25 nM) and/or D3 (10 M) in saline, macromolecular leakage was monitored for 20 min as previously described (45,46).…”
Section: Analysis Of Microvascular Leakage By Intravital Microscopymentioning
confidence: 99%
“…FITC-dextran (70 kDa; Sigma-Aldrich) was injected at 10 mg/kg body weight into the retro-orbital plexus as a plasma tracer to permit visualization in fluorescence light of changes in vascular permeability. After topical application of FXIIa (25 nM) and/or D3 (10 M) in saline, macromolecular leakage was monitored for 20 min as previously described (45,46).…”
Section: Analysis Of Microvascular Leakage By Intravital Microscopymentioning
confidence: 99%
“…Expression of adhesion molecules and tissue factor, release of chemokines, increased permeability are some of the responses of ECs to these factors (Bossi et al, 2004;Dobrina et al, 2002;Kilgore et al, 1996;Selvan et al, 1998) and both C5a and SC5b-9 have been shown to promote transendothelial migration of PMN (Dobrina et al, 2002). However, under normal conditions the endothelium is protected from the stimulating effect of C activation products that induce a pro-inflammatory and pro-coagulant state by the regulatory proteins CD46, CD55 and CD59 expressed on their surface and the fluid phase regulator Factor H that binds to ECs (Asch et al, 1986;Hamilton et al, 1990;Jokiranta et al, 2005;McNearney et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…В последние годы изучаются но вые роли контактных факторов, их ингибиторов в фи зиологических и патологических процессах, в частности при воспалительных реакциях различной этиологии. Установлены возможности альтернативной «неконтактной» активации СФХ, участие эндотелия, тромбоцитов и лейкоцитов в патологических реакциях этой системы, так же исследуются пути коррекции ее недостаточности или гиперфункции [3][4][5][6][7]. Для углуб ления представлений о функционировании системы фактора Хагемана в остром периоде ТЧМТ целесооб разным представляется изучение динамики и взаимо связей контактных факторов, их ингибиторов с гло бальными показателями гемокоагуляции, фибринолиза и реактантами воспаления.…”
Section: адрес для корреспонденции (Correspondence To)unclassified